MiR-92a-1-p5 Modulated Expression of the flightin Gene Regulates Flight Muscle Formation and Wing Extension in the Pea Aphid, Acyrthosiphon pisum (Hemiptera: Aphidoidea). Issue 3 (23rd June 2022) - Chang, Meiling; Cheng, Hao; Cai, Zhiyan; Qian, Yuxin; Zhang, Kun; Yang, Linlin; Ma, Na; Li, Dandan
Abstract: Aphids exhibit wing polyphenism. Winged and wingless aphid morphs are produced by parthenogenesis depending on population density and host plant quality. Recent studies showed that microRNAs in alate and apterous individuals have differential expression and are involved in wing dimorphism of Acyrthosiphon pisum . From which miR-92a-1-p5 can target the mRNA of flight muscle gene flightin in vitro, but what effect they have on wing development of aphid is unclear. Here with the nanocarrier-delivered RNA interference (RNAi) method, flightin gene was knocked down in winged nymphs of A . pisum . Results showed that the majority (63.33%) of adults had malformed wings, the shape of dorsal longitudinal muscle (DLM) was deformed severely, the dorsoventral flight muscle (DVM) became wider and looser in aphids with flightin reduction compared with the negative control. Overexpression of miR-92a-1-p5 caused decreased expression of flightin and malformed wings of aphids, with a mutant ratio of 62.50%. Morphological analysis of flight musculature showed the consistent result as that with flightin knockdown. These results suggest that flightin is essential for flight musculature formation and wing extension in A . pisum, which can be modulated by miR-92a-1-p5.